PENILAIAN DAMPAK LINGKUNGAN PROSES PRODUKSI TAHU DI JAKARTA BARAT MENGGUNAKAN METODE LIFE CYCLE ASSESSMENT - Indah Permata Sari; Ferren Liling Sia; Anik Nur Habyba; Wawan Kurniawan (Universitas Lambung Mangkurat, 2022)
The Indonesian population likes and demands processed soy products like tofu and tempeh. The daily mass production of tofu may have a detrimental effect on the environment. Using the Life Cycle Assessment approach, this study examines the environmental impact of the tofu production process in West Jakarta from cradle - to - grave. The 35 kg of tofu produced in each production batch served as the study's functional unit. The process of cultivating and transporting soybeans to the factory was included in the environmental impact analysis process. Tofu production data which includes washing, soaking, milling, cooking, screening, clumping and printing tofu were obtained from observational data, interviewing, and inventory data. and inventory data of the tofu production process. The equipment used such as plastic, stainless steel and wood tools are taken into account in the environmental impact analysis by taking into account the service life. The environmental impacts analyzed include the potential for global warming (GWP), acidification, the potential for depletion of the ozone layer (ODP), and eutrophication. Using Simapro software, environmental impact analysis was performed using the CML-IA methodology. The analysis's findings indicate that the following environmental effect values were produced: GWP of 34.2 kg CO2 eq, acidification of 0.0551 kg SO2 eq, ODP of 5.44E-7 kg CFC-11 eq, and eutrophication of 0 kg PO4 eq. The process of cultivation and transportation of soybeans to the factory was the biggest contributor to the potential for global warming in tofu production.